Structure and properties of powder gas-plasma coatings based on nickel - Hlushkova, D.B.; Bagrov, V.A.; Demchenko, S.V.; Volchuk, V.M.; Kalinin, O.V.; Kalinina, N.E. (Вопросы атомной науки и техники, 2022)
The development of modern technology requires a constant increase in reliability and durability of products. Widely used in the practice of domestic and foreign engineering coatings from electrolytic chromium for several hundred hours are triggered, they are unsatisfactorily working on friction and wear at high temperatures. The subject of the study were powder materials based on nickel PG-SR3 and PG-SR4. The work is devoted to the study of the formation of gas-plasma coatings on parts of the cylinder-piston group of internal combustion engines using self-fluxing powders based on nickel, as well as the structure and properties change after coating sputtering, its reflow, subsequent hardening. The purpose of this work is to study powder materials applied to the working surfaces of piston rings by gas-thermal spraying. The object of the study are processes of formation of the structure and properties of coatings from powder materials. The presence in the deposited layer of a solid solution based on nickel, carbide phase, borides of chromium and nickel, chromium silicides is established. The greatest macro- and microhardness is possessed by fused layers containing the greatest number of strengthening phases. The conducted researches and industrial tests allowed to introduce the coating into production. Розвиток сучасної техніки потребує постійного підвищення надійності та довговічності виробів. Широко застосовувані в практиці вітчизняного та зарубіжного машинобудування покриття з електролітичного хрому за кілька сотень годин спрацьовуються, вони незадовільно працюють на тертя та зношування за високих температур. Предметом дослідження були порошкові матеріали на основі нікелю ПГ-СР3 та ПГ-СР4. Робота присвячена дослідженню формування газоплазмових покриттів на деталях циліндропоршневої групи двигунів внутрішнього згоряння з використанням самофлюсованих порошків на основі нікелю, а також зміні структури та властивостей після напилення покриття, його оплавлення, наступного загартування. Мета роботи – дослідження порошкових матеріалів, які нанесені на робочі поверхні поршневих кілець газотермічним напиленням. Об’єктом дослідження є процеси формування структури та властивостей покриттів із порошкових матеріалів. Встановлено наявність у напиленому шарі твердого розчину на основі нікелю, карбідної фази, боридів хрому та нікелю, силіцидів хрому. Найбільшу макро- і мікротвердість мають оплавлені шари, що містять найбільшу кількість зміцнювальних фаз. Проведені дослідження та промислові випробування дозволили впровадити покриття у виробництво.